Utilization of Hydroxyapatite-Chitosan-Bay Leaf Oil (Syzygium Polyanthum W.) as Antibacterial for Streptococcus Mutants - Adriani, Sherly Wahyu; Cahyaningrum, Sari Edi (Jurnal Pijar Mipa, 2024)
Dental caries is a disease that can damage hard tooth tissue caused by the activity of Streptococcus mutans bacteria. Streptococcus mutans bacteria are the leading cause of dental caries disease. Efforts to prevent dental caries can be made using toothpaste, but toothpaste cannot reach areas that are difficult to reach with a toothbrush. Another method that can be used is mouthwash. This study was developed with the active ingredient compound HAp-chitosan-bay leaf oil in mouthwash to have an antimicrobial effect to prevent dental caries. This study aimed to determine the chemical physics characteristics and antibacterial activity of mouthwash preparations based on hydroxyapatite-chitosan-bay leaf oil. In this study, the active ingredients hydroxyapatite-chitosan-bay leaf oil was used with variations in the concentration of bay leaf oil, namely 0.5, 1.5, and 2.5 %. FT-IR characterization showed the presence of OH, N-H, CH, C=O, C=C, C-O, and PO43- functional groups. The pH test on the mouthwash showed compliance with the quality standard for mouthwash pH, which has a pH range of 5-7. The homogeneity test results in the mouthwash preparation showed no sediment or separation. Antibacterial activity testing showed that the HAp-chitosan-bay leaf oil mouthwash preparation inhibited the growth of Streptococcus mutans bacteria. The inhibition zone in the strong category with an average of 12.75 mm was shown in the HAp-chitosan-bay leaf oil mouthwash preparation formulation with a concentration of 2.5% bay leaf oil with the addition of sodium lauryl sulfate (SLS).